2021
DOI: 10.1542/peds.2021-050875
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Executive Function in Congenital Heart Disease: A Meta-analysis

Abstract: CONTEXT Cognitive function and executive function (EF) impairments contribute to the long-term burden of congenital heart disease (CHD). However, the degree and profile of impairments are insufficiently described. OBJECTIVE To systematically review and meta-analyze the evidence on cognitive function and EF outcomes in school-aged children operated for CHD and identify the risk factors for an unfavorable outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 138 publications
4
67
0
Order By: Relevance
“…This finding may reflect the greater disease severity, greater intensity of PICU treatments, and/or greater intensity of surgical treatment(s) of children admitted after heart- or heart–lung transplantation. The results on the PICU subgroups in the current study are in line with earlier literature overviews [ 36 42 ] and extend these findings by the unique focus on children admitted to the PICU and by providing comprehensive meta-analytic quantification of intelligence impairment.…”
Section: Discussionsupporting
confidence: 90%
“…This finding may reflect the greater disease severity, greater intensity of PICU treatments, and/or greater intensity of surgical treatment(s) of children admitted after heart- or heart–lung transplantation. The results on the PICU subgroups in the current study are in line with earlier literature overviews [ 36 42 ] and extend these findings by the unique focus on children admitted to the PICU and by providing comprehensive meta-analytic quantification of intelligence impairment.…”
Section: Discussionsupporting
confidence: 90%
“…The latest studies on diffusion tensor imaging have shown extensive persisting white matter changes 28,59,60 to be associated with neurodevelopmental outcome up to 30 months of age. 59 We were unable to replicate the finding of a large meta-analysis 8 demonstrating that more severe CHD complexity was associated with poorer neurodevelopmental outcome. However, this is most likely due to the small sample size of our cohort and the relatively few patients with single ventricle physiology.…”
Section: Discussionmentioning
confidence: 82%
“…1 In recent decades, the survival rate has increased to 85% to 90% due to improved surgical and perioperative management. [2][3][4] However, CHD patients are at risk of delayed neurodevelopment affecting cognition, language, motor function, [5][6][7][8] and executive function 8,9 during childhood and into adolescence [5][6][7][8][9] and adulthood. 10 Evidence is increasing that brain immaturity, 11 smaller brain volumes, [12][13][14][15] and perioperative brain injury 12,[16][17][18] are related to altered neurobehavior during the neonatal period 14,15 and delayed neurodevelopment during early childhood.…”
mentioning
confidence: 99%
“…In contrast to these findings, one study reported higher rehabilitation service use in adolescents with CHD than in adolescents born VPT. 18 The imbalance in the number of therapies between these 2 clinical groups, regardless of the direction of imbalance, is inconsistent with the comparable extent of neurodevelopmental deficits that both clinical groups face as evidenced by the current and numerous previous studies (eg, 5,6,[8][9][10][11]13 ). In the current study, the lower prevalence of motor therapies in children with CHD was particularly misaligned with the pronounced motor problems apparent in these children.…”
Section: Discussionmentioning
confidence: 72%